Kelimpahan Makrozoobentos di Perairan Situ Pamulang - Alfin, Edward (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2014)
The research on the abundance of macrozoobenthos in Situ Pamulang waters conducted in August 2014. This study aims to determined the types of macrozoobenthos and abundance in the region. This study used survey method with sampling at three (3) points by using purposive random sampling in Situ Pamulang waters. The results were obtained nine types of macrozoobenthos that overall there in 4 orders are 5 types of orders Sorbeoconcha, 2 types of orders Viviparoidea and each one kind of order Architaenioglossa and Hygrophyila. The abundance of macrozoobenthos between 25-2225 individuals/m2. Macrozoobenthos including low diversity index was 1.48. Macrozoobenthos dominance index of 0.25 so that it can be said there was no type that dominates in the region.